Impacts of a warming Arctic : Arctic Climate Impact Assessment - Hassol, Susan Joy.; Arctic Climate Impact Assessment; Arctic Monitoring and Assessment Programme; Program for the Conservation of Arctic Flora and Fauna; International Arctic Science Committee (Cambridge, U.K. : Cambridge University Press, 2004)
A summary of the Arctic Climate Impact Assessment (ACIA), a comprehensive examination of climatic changes in the Arctic Region and what they may portend globally. The ACIA is based on five climate models, findings from hundreds of Arctic researchers worldwide, and perspectives of Arctic Indigenous Peoples
Context -- Executive summary: Arctic climate change and its impacts -- Key findings -- Arctic climate trends -- Impacts on natural systems -- Impacts on society -- Sub-regional impacts -- Supporting evidence for the key findings: Arctic climate change -- Global implications -- Vegetation changes -- Animal species shifts -- Coastal impacts -- Marine transportation -- Thawing ground -- Indigenous communities -- Ultraviolet radiation -- Multiple stresses -- Selected sub-regional overview -- Improving future assessments -- Concluding thoughts
'ACIA [Arctic Climate Impact Assessment] is a project implemented by AMAP [Arctic Monitoring and Assessment Programme], CAFF [Conservation of Arctic Flora and Fauna], and IASC [International Arctic Science Committee]'--Pref
Also available on the Internet. Viewed: 11/10/2004
Mode of access: World Wide Web
Keywords: Climatic changes -- Arctic Regions; Habitat (Ecology) -- Arctic Regions; Sea ice -- Arctic Regions; Greenhouse gases -- Arctic Regions; Ultraviolet radiation -- Arctic Regions; Indigenous peoples -- Ecology -- Arctic Regions; Global warming; Global environmental change; Arctic regions -- Environmental conditions; Arctic regions -- Climate